TECTONIC EVOLUTION OF THE NORTHERN MARGIN OF THE CENOZOIC ARARAT BASIN, LESSER CAUCASUS, ARMENIA. (26th September 2018) - Avagyan, A.; Sosson, M.; Sahakyan, L.; Sheremet, Y.; Vardanyan, S.; Martirosyan, M.; Muller, C.
Abstract : This paper investigates the structure of the northern margin of the Ararat depression in a study area in SE Armenia. The depression is a Cenozoic intermontane basin located to the south of the Lesser Caucasus. The purpose is to improve understanding of the basin's structure and origin within a regional tectonic framework which has been dominated since the Late Cretaceous by the closure of Neotethys and the Arabia‐Eurasia collision. We suggest that the depression is not a graben controlled by normal faults; rather, based on detailed observations, structures in the study area are interpreted as oblique‐slip reverse and thrust faults activated in post Oligocene‐Miocene times. These compressional faults resulted in the formation of asymmetric fold structures including the Lanjanist and Urts anticlines which are well expressed in the surface relief to the north of the Ararat depression. In general the structural pattern is complicated by secondary normal faults which resulted in superimposed gravitational slope processes and erosion. Major structures in the study area originated in a compressional setting associated with the closure of Neotethys since the latest Cretaceous. Post‐collisional strike‐slip faulting was linked to convergence of the Arabian and Eurasian plate margins. Pliocene and Quaternary structures, some still active, show evidence of structural inheritance. The Armenian portion of the Ararat depression contains obduction‐related nappes, anticlines and thrust faults which have potential as structural traps for hydrocarbons. These should be investigated in detail using advanced geophysical methods including 2D and 3D seismic analyses.